Factors Affecting the Rate of CaCO3 Precipitation in Biocementation of Heavy Metal Contaminated Soil - Makinda, Jodin (International Journal of Integrated Engineering, 2025)
Ground improvement methods using physical and chemical treatments are considered effective but costly, involving large engineering work and may pose serious environmental problems. Therefore, biocementation using enzyme-induced calcite precipitation (EICP) technique is introduced. The efficiency of EICP is influenced by the production of calcite carbonate, CaCO3 and governed by multiple factors. While some preliminary studies have been done on variety of soil types, none the them were performed on heavy-metal contaminated soil. This paper presents the research conducted on factors affecting the CaCO3 precipitation in biocementation of mining waste collected from a copper mine in Sabah, Malaysia treated using EICP solution, cured in a leaching cell and tested using inductively coupled plasma optical emission spectroscopy and acid washing test. Results concluded that factors affecting the production of calcite carbonate content are the cementation concentration (1.0M > 0.5M), degree of compaction (70% MDD> 80% MDD) and curing temperature (25 ⁰C > 15 ⁰C > 5 ⁰C). Meanwhile, immediate production is observed (1-day curing) indicating that curing time is not a significant factor. Hence, the results proposed that the optimum production of CaCO3 for treatment of heavy metal in contaminated soils is at cementation solution of 1.0M, compacted at 70% MDD and cured at 25 °C temperature.